How perceptions of raw data collection affect intelligence accountability: the Danish intelligence field - Hartvigsen, Melanie Sofia (Frontiers in Political Science, 2025)
The collection of raw data has become a central aspect of intelligence accountability. This study investigates the relationship between perceptions of raw data collection and intelligence accountability virtues within a coherent framework, aiming to provide a more comprehensive understanding of how intelligence accountability systems are prioritised and justified. The research combines discussions on the ethics of bulk collection of raw data and civil rights with the literature on intelligence accountability and applies this to the Danish case within an organisational fields framework. Empirically, the study draws on interviews and document analysis to examine how different actors within the Danish intelligence field understand and position themselves in relation to raw data collection. The findings demonstrate that actors adopt divergent positions on the collection of raw data, and that these positions shape their understandings of intelligence accountability and influence how they prioritise accountability systems. Furthermore, the study shows that support from political decision-makers for certain actors is decisive in determining the distribution of power within the intelligence field.